Keterkaitan jumlah wisatawan mancanegara, tingkat hunian hotel, PDRB, dan pendapatan asli daerah: Bukti dari Provinsi Kalimantan Barat - Kue, Renata; Kartika, Metasari (Journal of Economics Research and Policy Studies, 2025)
Tourism is a rapidly developing industry in many countries. Tourism is a sector with the potential to drive the development of the national and regional economy, and it is also one of the key sectors contributing to the increase in PAD. West Kalimantan Province has tourism potential that needs to be explored, enabling the regional economy to develop rapidly. Using quantitative descriptive methods, analyzed with panel data regression. The results of this study indicate that the variables of the number of foreign tourists and hotel occupancy rates have a positive, yet insignificant, effect on regional original income. In contrast, the variable of gross regional domestic product has a positive and significant effect on regional original income. Simultaneously, the variables of the number of foreign tourists, hotel occupancy rates, and gross regional domestic product have a positive and significant effect on regional original income in West Kalimantan Province from 2014 to 2023. These findings can be used to support the formulation of regional economic policies related to the important role of the tourism sector in efforts to increase local revenue (PAD).